ENTREPRENEURIAL APPROACHES TO SUSTAINABILITY IN THE CIRCULAR ECONOMY IN NIGERIA (Journal of the Management Sciences, 2025)
The study aims to examine the extent to which entrepreneurs in Delta State incorporate sustainability into their operations, identify adopted circular business models, evaluate perceived benefits and challenges, and analyze how entrepreneurial strategies and innovation influence CE adoption. The study employs a deductive approach and quantitative design to test theoretical constructs empirically. A structured questionnaire titled Entrepreneurial Sustainability and Circular Economy Questionnaire (ESCEQ) was developed, validated by experts, and distributed both physically and digitally. Using stratified random sampling, data were collected from 120 entrepreneurs across five sectors (e.g., recycling, sustainable packaging). The instrument demonstrated strong internal consistency with Cronbach’s Alpha scores exceeding 0.70. Data were analyzed using SPSS (version 26), employing descriptive statistics, correlation, and regression analyses to evaluate relationships between key variables. Harman’s single-factor test confirmed the absence of significant common method bias.Results revealed a significant positive relationship between sustainability integration, circular business model adoption, perception of benefits and challenges, and entrepreneurial strategies with CE adoption. Entrepreneurial innovation was the most influential predictor (β = 0.3125). The regression model explained 56.2% of variance in CE adoption (R² = 0.5623). Entrepreneurs in Delta State demonstrate strong engagement with circular economy principles. However, barriers such as limited financing and awareness persist. The study recommends government incentives, educational reforms, NGO-led training, and enhanced entrepreneur collaboration. This study contributes empirical insights into circular entrepreneurship in Nigeria, offering actionable strategies for policymakers, educators, and entrepreneurs to foster sustainable economic development.
Keywords: Circular Economy; Sustainability; Entrepreneurship; Innovation; Sustainable Development; Business Models